Kepemimpinan Instruksional Kepala Sekolah Literature Review - Putri, Egiska Lusita; Sucitra, Diah Ayu (9 772338317006, 2024)
Abstract: Principal Instructional Leadership; Literature Review. This study uses the Literature review method which aims to determine how much the role of the principal in the success of instructional leadership. The samples used in this study were 24 journals consisting of national and international journals. The results of this study show that the role of the principal as a school leader is very important in instructional leadership because the principal as a school leader holds a position that has a big role in maintaining and improving the quality of learning in schools. In addition, teachers' teaching performance can be improved by improving principals' performance. It can be concluded that the principal's instructional leadership is an effective leadership.Keywords: principal instructional leadership; literature reviewDOI: 10.23960/jmmp .v12.i1.2024.03